Fabrication and Characterization of Tri Metal Oxides by Chemical Spray Pyrolysis Technique as a Gas Sensor - Othman, Farhad M.; Abdul-hamead, Alaa A.; Ali, Noor M. (Al-Khwarizmi Engineering Journal, 2017)
In this research tri metal oxides were fabricated by simple chemical spray pyrolysis technique from (Sn(NO3)2.20 H2O, Zn(NO3)2.6 H2O, Cd(NO3)2.4 H2O) salts at concentration 0.1M with mixing weight ratio 50:50 were fabricated on silicon substrate n-type (111). (with & without the presence of grooves by the following diemensions (20μm width, 7.5μm depth) with thickness was about ( 0.1 ±0.05 µm) using water soluble as precursors at a substrate temperature 550 ºC±5, with spray distance (15 cm) and their gas sensing properties toward H2S gas at different concentrations (10,50,100,500 ppmv) in air were investigated at room temperature which related with the petroleum industry. Furthermore structural and morphology properties were inspecting. Experimental results show that the Zn2SnO4 and Cd2SnO4 thin films were achieved from the used salts and samples gas sensitivity which improved with the presence of substrate grooves. Which make the sensor suitable for the detection of lower .concentrations of hazard H2S gas in the petroleum industry.